Effects of establishing a multidisciplinary pancreatic cancer clinic on time-to-treatment. Issue 28 (1st October 2022) - Vaghjiani, Raj; Sarkar, Joy; Stiles, Zachary; Pangelinan, Jennifer; Iyer, Renuka V.; Calvo, Benjamin F.; Kukar, Moshim; Hochwald, Steven N.; Malik, Nadia Karen; Fountzilas, Christos; Alarcon Velasco, Sylvia Vania; Cherkassky, Leonid
Abstract : 61 Background: Despite recent advances, pancreatic cancer remains an exceedingly morbid disease. This is often attributed to the lack of effective screening tools and the consequent late presentation of patients. The best prognosis is reserved for patients with resectable tumors thus highlighting the importance of swift evaluation and the initiation of treatment following a diagnosis. Multidisciplinary clinics allow for the expedient evaluation of patients by different subspecialties in the same day. Methods: A newly designed, multidisciplinary workflow (MDC-multidisciplinary care clinic) for patients recently diagnosed with pancreatic adenocarcinoma was established at a single, tertiary-care comprehensive cancer center in September of 2021. Patients presenting to MDC undergo same day consultation by surgical oncology, medical oncology, receive genetics counseling and testing, nutrition counseling, and additional support services as indicated. Patients from a prospectively maintained database were compared from before (n = 14) and after (n = 30) implementation of the new workflow. Average time to provider consultation, port placement, and initiation of neoadjuvant chemotherapy were compared using student's t-test. Results: After a biopsy diagnosis of pancreatic adenocarcinoma, the time interval from initial surgical consultation to initial medical oncology consultation improved from 7d to 1d ( p =.003) with the implementation of MDC. Over 90% of patients were seen on the same day after the MDC was established, compared to just 7% before. There was no difference in the time from initial biopsy diagnosis to initial surgical consultation, biopsy to initial medical oncology consultation, biopsy to port placement, or biopsy to chemotherapy initiation. Conclusions: In this early experience with a new pancreatic cancer multidisciplinary clinic, patients experienced improvements in time to subspecialty evaluation by nearly 7 days. Additionally, prospective data on oncologic outcomes and patient quality-of-care metrics are ongoing; however, this quality improvement effort has already reduced patient burdens in accessing timely care. Our continued efforts focus on further improving care coordination along the entire patient cancer care trajectory.